Genetic Insights of Cholesterol and Atherosclerosis; Complex Biology - Jadhav, Kishan L; Kapare, Priyanka R; Khairmode, Divya V; Keskar, Chaitali H; Mali, Akash S (Journal of Diseases, 2018)
Atherosclerosis is multifaceted arterial disease involving collaboration of chromosomal and conservational factors; around seven million Americans are experiencing a heart attack during their lifetime. Many biomolecules play different roles in atherosclerosis such as 5-LO enzyme which play vital role in synthesis of leukotriene’s inflammatory intermediates and proteins. Previous studies show that individuals suffering from coronary artery disease more commonly have C. pneumonia antibody than inhabitant’s controls. In recent years the genes and genetic polymorphism which are associated with atherosclerosis had been identified. Phospholipid transfer protein will subsequently decrease the HDL mass and cholesterol efflux capacity due to its overexpression and deletation. Our aim of this review is to demonstrate complex biology of atherosclerosis and effect of cholesterol in cardiovascular diseases.